Cannabis use behaviors and prevalence of anxiety and depressive symptoms in a cohort of Canadian medicinal cannabis users. (April 2019) - Turna, Jasmine; Simpson, William; Patterson, Beth; Lucas, Philippe; Van Ameringen, Michael
Abstract: Cannabis is commonly used recreationally for its euphoric and relaxing effects, while its medical use is permitted in several jurisdictions. With only low-quality evidence suggesting anxiolytic effects of cannabis and strong public sentiment surrounding such purported effects, the purpose of this study was to examine the prevalence of cannabis for medicinal purposes (CMP) use for anxiety symptoms. An online survey was disseminated to CMP users registered with a Canadian licensed producer. Respondents completed demographic and validated self-report questionnaires (GAD-7, PHQ-9, MINI-SPIN, and panic disorder/agoraphobia DSM-5 criteria). Cannabis use behaviors were also discussed. Overall, 2032 completed responses with a verified user number were collected. Of the total sample, 888 (43.7%) reported CMP authorization to treat anxiety symptoms and completed all psychometric screening instruments. Rates of probable disorders were high (Generalized Anxiety Disorder: 45.6%, Social Anxiety Disorder: 42.4%, Major Depressive Disorder: 25.7%, Panic Disorder/Agoraphobia: 25.7%); 63.4% met screening criteria for ≥1 disorder. Most (92%) reported that cannabis improved their symptoms, despite continuing to endorse moderate-level severity. Nearly half (49%) reported replacing a non-psychiatric (53.7%) or psychiatric medication (46.3%) prescribed to them by their physician with CMP. Respondents endorsed daily CMP use and severity of anxiety (GAD-7, p < 0.001) and depressive (PHQ-9, p < 0.001) symptoms were positively associated with the amount of cannabis used/day. The vast majority perceived symptom improvement with CMP use and did not believe CMP use was associated with impairment or an inability to control use. Nevertheless, the possibility of cannabis use disorder cannot be ruled out as well as the possibility that improvements in non-psychiatric conditions were attributed to improvements in anxiety. These results highlight the need to systematically evaluate CMP use for mental illness.